Uso racional da água em plantios de limão tahiti, citrus latifolia (Yu. Tanaka), na Amazônia Oriental. - SILVA JUNIOR, Alberto Cruz da Silva (Universidade Federal do Pará, 2025)
The need for a more rational use of water resources requires changes in society's behavior in favor of a more sustainable use of natural resources. This interdisciplinary research investigated how soil-plant-atmosphere interactions modify the energy balance and evapotranspiration demand in Tahiti lime plantations and how these variations interfere in the water sustainability of the crop in the eastern Amazon. The specific objectives are to evaluate the seasonality of the energy balance and the water demand of the Tahiti lime and to define parameters that contribute to the efficient use of water in irrigation in the Eastern Amazon. In addition, calculate the green, blue and gray water footprints of lemon production in the region and compare with the main producing regions in Brazil. With the results of this thesis, it is expected to contribute to generate a solid base of information that allows optimizing the replacement of water in irrigation and quantifying the size of human appropriation of this natural resource in the areas of cultivation. Meteorological data were monitored: air temperature at two levels above the canopy, relative air humidity, extraterrestrial radiation, wind speed and direction, rainfall and heat flux to the ground; soil data: granulometry, chemical fertility, bulk density and volumetric soil water content; and data inherent to the plant: effective depth of the root system, flowering, fruiting and leaf area index. We also use IBGE, INMET, ANA and MAPBIOMAS databases as a source for calculating the water footprints of tahiti lime production in 48 municipalities in 4 states, correlating their respective PH's with government water security indices and thus evaluating the sustainability of production. As main results of chapter 2 it was found that 63% of the available energy was used to produce latent heat in the wettest period, while 60% were used during the less rainy season. Sensible heat used 32% and 34% during the most and least rainy period, respectively. On the other hand, soil heat showed little variation, with an average of 5% for the entire period. The water consumption of Tahiti lime during the experiment was 1599 mm, with a daily mean of 3.70 mm day-1, while the mean value of Kc was 1.4. These results allow the adequate design of water supply protocols for culture in the main citrus pole in the Amazon region. In chapter 3, the main findings are that there is wide variability in PH among the producing municipalities, with emphasis on the states of São Paulo and Minas Gerais, where the best results were obtained. In the states of Bahia and Pará, we found high PH's associated mainly with low productivity. In general, we conclude that the seasonality of the evapotranspiration demands of the lemon crop follow specific dynamics in the Amazon region and that the water footprint was a good gauge of water appropriation during the production of tahiti lemon.